Transcatheter Tricuspid Valve-In-Ring and Aortic Valve-In-Valve Implantation - Reichart, Daniel; Schofer, Niklas; Deuschl, Florian; Schaefer, Andreas; Blankenberg, Stefan; Reichenspurner, Hermann; Schaefer, Ulrich; Conradi, Lenard (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background Transcatheter heart valve (THV) therapies have shown to be an alternative to surgical valve replacement, especially in high-risk patients requiring redo surgery. However, reports of transcatheter-based interventions in tricuspid valve position are scarce.Case Description Here, we report a case of successful concomitant transcatheter aortic valve-in-valve (ViV) and tricuspid valve-in-ring (ViR) procedures using a 23-mm CoreValve Evolut R THV (Medtronic, Inc., Minneapolis, Minnesota, United States) in aortic position and a 29-mm SAPIEN3 (Edwards Lifesciences, Inc., Irvine, California, United States) THV in tricuspid position.Conclusion This case demonstrates feasibility of concomitant transcatheter aortic ViV and tricuspid ViR procedures.
Keywords: aortic valve; tricuspid valve; heart valve